2014
DOI: 10.1039/c4ce00150h
|View full text |Cite
|
Sign up to set email alerts
|

Positions of amino groups on ammonium salts tunes the conformations of crown ethers: crystal structures, Hirshfeld surfaces and spectroscopic studies

Abstract: The position of the amino group on the ammonium salt plays a key role in the supramolecular structure and conformation of the crown ether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…It may be noted that the so-called strong synthons, such as carboxylic acid dimer, amide dimer, etc., have interaction energies around 60–70 kJ·mol –1 . A well-known supramolecular recognition unit involving 18-crown-6 and organic moieties is the ammonium cation:18-crown-6 motif. The interaction energies for these motifs have been found to be around 200–270 kJ·mol –1 . While these very high interaction strengths are due to the cationic binding, the corresponding neutral amine:18-crown-6 binding strengths have been found to be in the range 45–70 kJ·mol –1 .…”
Section: Resultsmentioning
confidence: 99%
“…It may be noted that the so-called strong synthons, such as carboxylic acid dimer, amide dimer, etc., have interaction energies around 60–70 kJ·mol –1 . A well-known supramolecular recognition unit involving 18-crown-6 and organic moieties is the ammonium cation:18-crown-6 motif. The interaction energies for these motifs have been found to be around 200–270 kJ·mol –1 . While these very high interaction strengths are due to the cationic binding, the corresponding neutral amine:18-crown-6 binding strengths have been found to be in the range 45–70 kJ·mol –1 .…”
Section: Resultsmentioning
confidence: 99%
“…47 In our previous work, we have investigated in detail the influence of substituents on the secondary interactions in crown ether-ammonium salt. 48 Herein, we report the influence of a magnetic field with different strengths (0.0, 0.5, 1.0, and 1.5 T) on the cocrystallization of 18-crown-6 (18-C-6) with 4,5dicyanoimidazole (4,5-dci), which results in different cocrystals 1-0.0T, 1-0.5T, 1-1.0T, and 1-1.5T (Scheme 1), respectively. Structural analysis revealed that the presence of an external magnetic field can result in elongating of the distance within cocrystals upon elongating.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The host–guest interaction between crown ethers and guest molecules is an important secondary interaction, which can be applied to mimic natural systems or construct new materials . In our previous work, we have investigated in detail the influence of substituents on the secondary interactions in crown ether-ammonium salt . Herein, we report the influence of a magnetic field with different strengths (0.0, 0.5, 1.0, and 1.5 T) on the cocrystallization of 18-crown-6 (18-C-6) with 4,5-dicyanoimidazole (4,5-dci), which results in different cocrystals 1 -0.0T, 1 -0.5T, 1 -1.0T, and 1 -1.5T (Scheme ), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been focused on the investigation of the reduction in the k of PIs . 18‐Crown‐6 (CE6) with annular pore structure had been employed to construct 18‐crown‐6‐polyimide complex (CE6‐PI) . The k of PI could be effectively reduced to 2.99 due to the shielding effect of low‐polarity CE6 on its strong polar imide groups .…”
Section: Introductionmentioning
confidence: 99%